Completed suicide among nursing home residents: a systematic review. (25th May 2015) - Murphy, Briony J.; Bugeja, Lyndal; Pilgrim, Jennifer; Ibrahim, Joseph E.
<x xml:space="preserve">Abstract</x> Objective The aim of this study is to systematically review published research describing the frequency, nature, and contributing factors of completed suicides among nursing home residents. Methods In accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Statement, this review examined all original, peer‐reviewed literature published in English between 1 January 1949 and 31 December 2013 describing completed suicides among nursing home residents. Information extracted for analysis included: study and population characteristics, method of suicide, potential risk factors, and interventions. Results Eight studies were identified; the majority (n = 5) conducted in the United States of America. There were 113 suicides in nursing homes reported in the literature, 101 with detailed information available for aggregate analysis. The majority were male (n = 62, 61.4%), aged between 61 and 93 years. Suicide was most commonly by hanging (n = 27, 38.0%) or falling from a height (n = 27, 38.0%). Risk factors were considered in a proportion of studies. Depression was examined in 27 cases and present in 18 (67%). Duration of residence was examined in 25 cases, 13 (52%) of which had resided in the nursing home less than 12 months. Physical health was examined in 22 cases, 11 (50%) of whom were experiencing physical decline. Prior suicidal behaviour, cognitive function, and personal loss were also examined. Organizational risk factors and intervention strategies were rarely considered. Conclusions There is a paucity of research describing completed suicide among nursing home residents. More large‐scale research is required using standardized methods for reporting information to better understand and prevent completed suicides in this setting. Copyright © 2015 John Wiley & Sons, Ltd.